When comes the spring - Oke, Janette, 1935- (Minneapolis, Minn. : Bethany House Publishers, 1985)
"Elizabeth and Wynn find that their commitment to God and to each other gives their life meaning. Can their love for each other sustain them through a harsh winter, loneliness, and rigors of life without any of the conveniences they're used to?"--Provided by publisher.
Keywords: Royal Canadian Mounted Police; Women pioneers -- Fiction; Canada, Western -- Fiction; Canada, Western -- Fiction; Christian fiction; Western stories; Love stories